1986
DOI: 10.1121/1.394327
|View full text |Cite
|
Sign up to set email alerts
|

Phase effects in masking related to dispersion in the inner ear

Abstract: Phase effects in masking experiments using multitone maskers are usually associated with strong variations in the masker envelope. In this article, psychoacoustic experiments with such maskers that lead to phase-dependent threshold variations of up to 20 dB, although the phase transformation leaves the envelope unchanged, are described. However, after filtering the maskers with a realistic basilar membrane model, the envelopes are different owing to the models phase-dispersive properties. Comparison of model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 9 publications
6
53
1
Order By: Relevance
“…Smith et al [1] measured the masked thresholds of a pure tone of frequency and phase identical to a Schroeder-phase masker component under conditions of controlled fundamental frequencies of masker and maskee frequencies. Kohlrausch and Sander [2] reported results for a sine-phase masker in addition to replicated experiments of Smith et al Both Smith and Kohlrausch discussed that the phase response of the auditory filter transforms the flat envelope of the input into an output containing marked peaks and dips, and that this leads to a substantial threshold variation between POS and NEG maskers.…”
Section: Masking Experimentsmentioning
confidence: 99%
“…Smith et al [1] measured the masked thresholds of a pure tone of frequency and phase identical to a Schroeder-phase masker component under conditions of controlled fundamental frequencies of masker and maskee frequencies. Kohlrausch and Sander [2] reported results for a sine-phase masker in addition to replicated experiments of Smith et al Both Smith and Kohlrausch discussed that the phase response of the auditory filter transforms the flat envelope of the input into an output containing marked peaks and dips, and that this leads to a substantial threshold variation between POS and NEG maskers.…”
Section: Masking Experimentsmentioning
confidence: 99%
“…This model was able to simulate the difference in masked threshold between POS and NEG observed in previous studies [1,2,4]. However, a large negative value is required for c, a parameter of the analytic gammachirp filter, in order to obtain the appropriate negative curvature of the phase function.…”
Section: Introductionmentioning
confidence: 96%
“…However, masked thresholds of a pure tone with frequency and phase identical to a component of the Schroeder-phase masker vary by approximately 20 dB between POS and NEG maskers [1,2]. Several studies [1][2][3][4][5] have reported that these masking differences are due to phase characteristics of the auditory filter. It has been reported that negative curvature of the auditory filter phase characteristics, that is, an upward frequency glide in the impulse response, creates pronounced peaks and dips in the POS waveform envelope.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BMTC are trains of up-chirps, with the instantaneous frequency of each single chirp moving from low to high frequencies. A relatively flat temporal response ͑slowly increasing and decreasing in time͒ in each single ͑local͒ auditory filter can be expected for upchirps since the stimulus phase curvature has the same sign as the curvature of the phase transfer function of the BM, at least at medium to high frequencies ͑see, e.g., Smith et al, 1986;Shera, 2001;Dau, 2001, 2004͒. The temporally inversed iBMTC are trains of down-chirps.…”
Section: Excitation Characteristics Of the Different Stimulimentioning
confidence: 99%